Prognostic factors for long-term quality of life after adjuvant radiotherapy in women with endometrial cancerPrognostische Faktoren für die langfristige Lebensqualität nach adjuvanter Radiotherapie von Frauen mit Endometriumkarzinom - Förster, Robert; Bruckner, Thomas; Arians, Nathalie; Rief, Harald; Debus, Jürgen; Lindel, Katja (Strahlentherapie und Onkologie, 2016)
BackgroundAdjuvant radiotherapy (RT) for endometrial cancer (EC) may affect patients’ quality of life (QoL). There is a paucity of data on prognostic factors for long-term QoL and sexual functioning. This study aimed to investigate such factors and assess the role of the vaginal dilator (VD).MethodsQoL was assessed in 112 EC patients 6 years (median) after RT. QoL was compared to normative data, and the influence of age, tumor characteristics, lymphadenectomy, RT, and acute toxicities was assessed. VD use and its effect on subjective vaginal shortening/tightness was analyzed.ResultsQoL was reduced, particularly in younger patients. Vaginal brachytherapy only and intensity-modulated RT (IMRT) were associated with better global health status and reduced chronic gastrointestinal (GI) symptoms. Higher acute GI toxicity was associated with increased chronic GI symptoms, particularly diarrhea, and reduced role functioning. Higher acute urinary toxicity was associated with increased chronic urological symptoms, muscular/pelvic pain, and chronic GI symptoms, as well as with reduced emotional/social functioning and reduced global health status. Sexual interest/activity was increased despite vaginal dryness and dyspareunia. Sexual interest/activity increased with age. Only few, mainly younger patients used the VD. VD use >1 year was found in women with higher sexual interest/activity. Acute vaginal toxicity and chronic pain prevented VD use. Subjective vaginal shortening/tightness was not reduced in VD users.ConclusionRT technique and acute toxicities are prognostic for the extent of chronic symptoms and long-term QoL. Sexuality is important even at a higher age. Few patients use the VD and a reduction of subjective vaginal shortening/tightness was not achieved.